Design Procedure of the Digital Educational Resources for Economic and Managerial Education of the Master’s in IT Students - Antoniuk, Dmytro; Vakaliuk, Tetiana (Educological discourse, 2024)
Design and implementation of the digital educational resources into educational process enables acquiring of the practical experience by the students, that is crucial to their career in IT. It also brings modern technologies and innovative approaches to education. As a result, it improves involvement of the students and helps drive their academic results up. It is important to consider the fact that a master’s in IT may often occupy managerial roles in their future career. Understanding of the economic and managerial principles is crucial for effective and efficient leadership. It is reasonable to conclude that digital educational resources containing knowledge and practical experiences from these areas drive the integrated approach in professional development of the target audience. The design procedure for developing of digital educational resources for economic and managerial education of the master’s in IT students is important for the development of the qualitative professionals. The proposed design procedure consists of seven stages. Stage 1 includes pedagogical and technological aspects. Stage 2 is the problem definition. The problem to be solved by the development of digital educational resource, the goal and particular tasks are being defined on this stage. Stage 3 contains the task for the development of the digital education resource. Stage 4 incorporates detailed design of the content and external appearance of the digital educational resource. Stage 5 represents interactive development and testing. Interactive processes allow progressive improvements and adaptation of the resource. Stage 6 requires start of pilot implementation and assessment of effectiveness. Stage 7 allows implementation of the digital educational resource, its interactive update and modification according to the feedback and usage results. Each stage of the procedure requires completion of the previous stages. At the same time an interactive nature of the stages of the procedure enables constant progressive improvement, update of the content and approaches used in the resource. Detailed planning and completion of the stages is needed for the success of the procedure.